A Sum Score to Define Therapy-Refractory Myasthenia Gravis: A German Consensus. (February 2021) - Schroeter, Michael; Berger, Benjamin; Blaes, Franz; Hagenacker, Tim; Jander, Sebastian; Kaiser, Julia; Kalischewski, Petra; Lee, De-Hyung; Ruck, Tobias; Schara, Ulrike; Urban, Peter; Meisel, Andreas
Background and purpose: In 2017, eculizumab has been approved for treatment-refractory generalised myasthenia gravis (TRgMG). The German Myasthenia Foundation has published a consensus statement on the use of eculizumab, with a recent update. However, a treatment-refractory state is still ill-defined and the term warrants further clarification. We aimed at developing a sum score to operationalise the definition of a TRgMG status, which is easy- to-handle in clinical decision making. Methods: We established a structured consensus process according to the Delphi consensus methodology, with 12 members of the medical advisory board of the German Myasthenia Foundation. Accordingly, 4 consensus rounds were accomplished. Additionally, a literature survey covering the years 2004-2020 was done and relevant information offered to the consensus group. Consensus criteria were predefined. In the consensus process the relative importance of scoring items were to be consented, with a sum score of 20 and above indicating a TRgMG status. Results: The sum score considers the categories disease severity, inefficiency of antecedent therapies, cessation of therapies due to side effects, and long term stay on the intensive care unit. Categories were specified by a total of 13 scoring items. Eventually, the Delphi process developed an unanimous scoring consensus. Conclusion: We suggest a sum score to define treatment refractory state in generalised myasthenia gravis. Beyond clarifying the indication of eculizumab, this easy-to-handle score facilitates clinical decision making and offers new inclusion criteria for clinical studies that explore new therapeutic perspectives in myasthenia gravis treatment.